Given the vertex of the parabola at point (2, -3):
The quadratic function in vertex form is:
f(x) = (x - 2)^2 - 3
where the vertex (h, k) is the minimum point = (2, -3).
Answer:
The answer in simplest term is 35.33333334.
Step-by-step explanation:
First, we need to divide 71 and 6.
71/6 = 23.66666667.
Now we need to divide 35 and 6.
35/6 = 11.66666667.
Now we need to add the two quotients.
23.66666667 + 11.66666667 = 35.33333334.
And that is the final answer.
I hope this helps!
![5(2 + d)](https://tex.z-dn.net/?f=5%282%20%2B%20d%29)
Since 5 is divisible by 10 and 5, we can factor out a 5 from both terms.
F(x) = -4(x - 2)² + 2
f(x) = -4((x - 2)(x - 2)) + 2
f(x) = -4(x² - 2x - 2x + 4) + 2
f(x) = -4(x² - 4x + 4) + 2
f(x) = -4(x²) + 4(4x) - 4(4) + 2
f(x) = -4x² + 16x - 16 + 2
f(x) = -4x² + 16x - 14
-4x² + 16x - 14 = 0
x = <u>-16 +/- √(16² - 4(-4)(-14))</u>
2(-4)
x = <u>-16 +/- √(256 - 224)</u>
-8
x = <u>-16 +/- √(32)
</u> -8<u>
</u>x = <u>-16 +/- 5.66
</u> -8<u>
</u>x = <u>-16 + 5.66</u> x = <u>-16 - 5.66
</u> -8 -8<u>
</u>x = <u>-10.34</u> x = <u>-21.66</u>
-8 -8
x = 1.2925 x = 2.7075
f(x) = -4x² + 16x - 14
f(1.2925) = -4(1.2925)² + 16(1.2925) - 14
f(1,2925) = -4(1.67055625) + 20.68 - 14
f(1.2925) = -6.682225 + 20.68 - 14
f(1.2925) = 13.997775 - 14
f(1.2925) = -0.002225
(x, f(x)) = (1.2925, -0.002225)
or
f(x) = -4x² + 16x - 14
f(2.7075) = -4(2.7075)² + 16(2.7075) - 14
f(2.7075) = -4(7.33055625) + 43.32 - 14
f(2.7075) = -29.322225 + 43.32 - 14
f(2.7075) = 13.997775 - 14
f(2.7075) = -0.002225
(x, f(x)) = (2.7075, -0.002225)
--------------------------------------------------------------------------------------------
f(x) = 2(x - 2)² + 1
f(x) = 2((x - 2)(x - 2)) + 1
f(x) = 2(x² - 2x - 2x + 4) + 1
f(x) = 2(x² - 4x + 4) + 1
f(x) = 2(x²) - 2(4x) + 2(4) + 1
f(x) = 2x² - 8x + 8 + 1
f(x) = 2x² - 8x + 9
2x² - 8x + 9 = 0
x = <u>-(-8) +/- √((-8)² - 4(2)(9))
</u> <u />2(2)
x = <u>8 +/- √(64 - 72)</u>
4
x = <u>8 +/- √(-8)</u>
4
x = <u>8 +/- √(8 × (-1))</u>
4
x =<u> 8 +/- √(8)√(-1)</u>
4
x = <u>8 +/- 2.83i</u>
4
x = 2 +/- 1.415i
x = 2 + 1.415i x = 2 - 1.415i
f(x) = 2x² - 8x + 9
f(2 + 1.415i) = 2(2 + 1.415i)² - 8(2 + 1.415i) + 9
f(2 + 1.415i) = 2((2 + 1.415i)(2 + 1.415i)) - 16 - 11.32i + 9
f(2 + 1.415i) = 2(4 + 2.83i + 2.83i + 2.00225i²) - 16 - 11.32i + 9
f(2 + 1.415i) = 2(4 + 5.66i + 2.00225) - 16 - 11.32i + 9
f(2 + 1.415i) = 8 + 11.32i + 4.0045 - 16 - 11.32i + 9
f(2 + 1.415i) = 8 + 4.0045 - 16 + 9 + 11.32i - 11.32i
f(2 + 1.415i) = 12.0045 - 16 + 9
f(2 + 1.415i) = -3.9955 + 9
f(2 + 1.415i) = 5.0045
(x, f(x)) = (2 + 1.415i, 5.0045)
or
f(x) = 2x² - 8x + 9
f(2 - 1.415i) = 2(2 - 1.415i)² - 8(2 - 1.415i) + 9
f(2 - 1.415i) = 2((2 - 1.415i)(2 - 1.415i)) - 16 + 11.32i + 9
f(2 - 1.415i) = 2(4 - 2.83i - 2.83i + 2.00225i²) - 16 + 11.32i + 9
f(2 - 1.415i) = 2(4 - 5.66i + 2.00225) - 16 + 11.32i + 9
f(2 - 1.415i) = 8 - 11.32i + 4.0045 - 16 + 11.32i + 9
f(2 - 1.415i) = 8 + 4.0045 - 16 + 9 - 11.32i + 11.32i
f(2 - 1.415i) = 12.0045 - 16 + 9
f(2 - 1.145i) = -3.9955 + 9
f(2 - 1.415i) = 5.0045
(x, f(x)) = (2 - 1.415i, 5.0045)
--------------------------------------------------------------------------------------------
f(x) = -2(x - 4)² + 8
f(x) = -2((x - 4)(x - 4)) + 8
f(x) = -2(x² - 4x - 4x + 16) + 8
f(x) = -2(x² - 8x + 16) + 8
f(x) = -2(x²) + 2(8x) - 2(16) + 8
f(x) = -2x² + 16x - 32 + 8
f(x) = -2x² + 16x - 24
-2x² + 16x - 24 = 0
x = <u>-16 +/- √(16² - 4(-2)(-24))</u>
2(-2)
x = <u>-16 +/- √(256 - 192)</u>
-4
x = <u>-16 +/- √(64)</u>
-4
x = <u>-16 +/- 8</u>
-4
x = <u>-16 + 8</u> x = <u>-16 - 8</u>
-4 -4
x = <u>-8</u> x = <u>-24</u>
-4 -4
x = 2 x = 6
f(x) = -2x² + 16x - 24
f(2) = -2(2)² + 16(2) - 24
f(2) = -2(4) + 32 - 24
f(2) = -8 + 32 - 24
f(2) = 24 - 24
f(2) = 0
(x,f(x)) = (2, 0)
or
f(x) = -2x² + 16x - 24
f(6) = -2(6)² + 16(6) - 24
f(6) = -2(36) + 96 - 24
f(6) = -72 + 96 - 24
f(6) = 24 - 24
f(6) = 0
(x, f(x)) = (6, 0)
<u />
Answer:
12
Step-by-step explanation:
The given geometric series is
![\sum_{n = 1}^{ \infty} 12( { - \frac{1}{9} })^{n - 1}](https://tex.z-dn.net/?f=%20%5Csum_%7Bn%20%3D%201%7D%5E%7B%20%5Cinfty%7D%2012%28%20%7B%20-%20%20%5Cfrac%7B1%7D%7B9%7D%20%7D%29%5E%7Bn%20-%201%7D%20)
We want to determine the first term of this geometric series.
Recall that the explicit formula is
![a_{n} = 12( { - \frac{1}{9} })^{n - 1}](https://tex.z-dn.net/?f=%20a_%7Bn%7D%20%3D%2012%28%20%7B%20-%20%20%5Cfrac%7B1%7D%7B9%7D%20%7D%29%5E%7Bn%20-%201%7D%20)
To find the first term, we put n=1 to get:
![a_{1} = 12( { - \frac{1}{9} })^{1 - 1}](https://tex.z-dn.net/?f=a_%7B1%7D%20%3D%2012%28%20%7B%20-%20%20%5Cfrac%7B1%7D%7B9%7D%20%7D%29%5E%7B1%20-%201%7D%20)
This gives us:
![a_{1} = 12( { - \frac{1}{9} })^{0}](https://tex.z-dn.net/?f=a_%7B1%7D%20%3D%2012%28%20%7B%20-%20%20%5Cfrac%7B1%7D%7B9%7D%20%7D%29%5E%7B0%7D)
![a_{1} = 12(1) = 12](https://tex.z-dn.net/?f=a_%7B1%7D%20%3D%2012%281%29%20%3D%2012)
Therefore the first term is 12